2021
DOI: 10.1002/cnr2.1559
|View full text |Cite
|
Sign up to set email alerts
|

Genetic features of B‐cell lymphoblastic lymphoma with TCF3‐PBX1

Abstract: Background Lymphoblastic lymphoma (LBL) and acute lymphoblastic leukemia (ALL) are categorized as the same entity under precursor lymphoid neoplasms in the World Health Organization classification. However, compared to B‐cell ALL, the molecular genetic makeup of B‐cell LBL remains to be understood, mainly due to its rarity. We performed whole exome sequencing (WES) on seven patients with TCF3‐PBX1 ‐positive B‐cell LBL. Methods WES was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This is considered an intermediate risk lesion in B-ALL as patients have favorable outcomes with modern, intensified chemotherapy regimens, but is reportedly associated with an increased risk of CNS relapse 8,13–15 . TCF3-PBX1 has been previously reported in several B-LLy patients 16,17 . All patients with TCF3-PBX1 fusion-positive B-LLy in prior studies had Stage III or IV disease, consistent with this group in which both patients had stage IV disease.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is considered an intermediate risk lesion in B-ALL as patients have favorable outcomes with modern, intensified chemotherapy regimens, but is reportedly associated with an increased risk of CNS relapse 8,13–15 . TCF3-PBX1 has been previously reported in several B-LLy patients 16,17 . All patients with TCF3-PBX1 fusion-positive B-LLy in prior studies had Stage III or IV disease, consistent with this group in which both patients had stage IV disease.…”
Section: Discussionsupporting
confidence: 81%
“…8,[13][14][15] TCF3-PBX1 has been previously reported in several B-LLy patients. 16,17 All patients with TCF3-PBX1 fusion-positive B-LLy in prior studies had Stage III or IV disease, consistent with this group in which both patients had stage IV disease. Of the 9 patients previously described in the literature, 3 patients relapsed, and 2 died of disease.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Shirai et al reported that, in this investigation, KMT2D mutations and 6q LOH were found to be recurring changes in seven patients with TCF3–PBX1 -positive B-LBL ( Shirai et al, 2022 ). Additional genetic mutations were found in the relapsed tumor that were not present in the primary tumor, including the 6q LOH.…”
Section: Overview Of Next-generation Sequencing Technologymentioning
confidence: 47%